Pengaruh Debt to Equity Ratio, Current Ratio dan Ukuran Perusahaan (Firm Size) Terhadap Return on Assets Pada Perusahaan Batubara Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2022-2024 - Mohammad Abdi Abdillah; Erwin Budianto (CV. ITTC INDONESIA, 2026)
The Indonesian coal mining industry faces pressures due to fluctuating global coal prices, rising operational costs, and energy transition policies that have led to declining company profitability. Therefore, capital structure management, liquidity, and company size are important factors suspected of influencing Return on Assets (ROA). However, previous research on the influence of Debt to Equity Ratio (DER), Current Ratio (CR), and Firm Size on profitability has shown inconsistencies. This study was conducted to examine the influence of Debt to Equity Ratio (DER), Current Ratio (CR), and Firm Size on Return on Assets in coal mining companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The focus of the study was to identify the influence of each independent variable, either partially or simultaneously, on Return on Assets. The study used a quantitative approach utilizing secondary data obtained from company financial reports during the observation period. The sample selection technique was carried out using a purposive sampling method, resulting in 18 coal mining companies that met the research criteria. Data analysis was carried out using classical assumption tests and multiple linear regression analysis. The results of this research test indicate that partially, the Debt to Equity Ratio has no significant effect on Return on Assets, the Current Ratio has no significant effect on Return on Assets, and Firm Size has a significant effect on Return on Assets. Meanwhile, the results of the simultaneous test show that the Debt to Equity Ratio, Current Ratio, and Firm Size have a significant effect on Return on Assets in coal mining companies listed on the Indonesia Stock Exchange for the period 2022-2024.